My Librarian Is a Camel: How Books Are Brought to Children Around the World - Ruurs, Margriet (Honesdale, Pa. : Boyds Mills Press, 2005)
Do you get books from a public library in your town or even in your school library? In many remote areas of the world, there are no library buildings. In many countries, books are delivered in unusual way: by bus, boat, elephant, donkey, train, even by wheelbarrow. Why would librarians go to the trouble of packing books on the backs of elephants or driving miles to deliver books by bus? Because, as one librarian in Azerbaijan says, "Books are as important to us as air or water!" This is the intriguing photo essay, a celebration of books, readers, and libraries.
New Kids Book 2022 Fall.
Keywords: Traveling libraries -- Juvenile literature; Librarians -- Juvenile literature; Traveling libraries; Libraries